Political strategies for policy reform - Birner, Regina; Gupta, Surupa; Sharma, Neeru (International Food Policy Research Institute, 2011)
Reforms of fertilizer subsidies and electricity supply to agriculture face different political challenges. As Chapter 7 shows, there are only a couple of methods, primarily technical, for addressing fertilizer reform that are unlikely to face political resistance. In electricity supply, a range of reform options may be adopted without significant political resistance, as outlined in Chapter 11. In both cases, several strategies may be used to overcome the political challenges of policy options that are likely to meet political resistance. The first section of this chapter discusses strategies that have been attempted and analyzed in the literature on the politics of economic reforms in India. The second section discusses strategies that could move beyond current reform efforts. The third section deals with the role of research-based knowledge, which is equally important for both types of political strategies.